KOMUNITAS KICAU MANIA DI KOTA PEKANBARU (Studi Kasus Pada Cipta Karya Bird Club) - Fakhri Syarif; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research analyze social fundalmental at Cipta Karya Bird Club in Pekanbaru. To get the appropriate and relevance data as per research purpose, the writer use qualitative descriptive approach by choosing the informants with purposive sampling. Based on the observation result and identification determine about five persons as subject of the research with their considerations as the active community members then often involved in various events. The result research shows Cipta Karya Bird Club formed because of the concern with the nearly extinct wild birds, especially Murai Batu, Kacer, and Cucak Ijo. The other reason is to strenghten friendship betwween members, society and bussines. Besides the samples has high level of trust between members, because they believe that things could make the club more advanced. Cipta Karya Bird Club actively involved in social events, like gotong royong and helping the poor community members, and building birds conservation. The good social relationship also with all the members of the same kinds of club. They often share information about health and growth of the birds. If there is a member who is got disfortune, usually Cipta Karya Bird Club members will help them, by donating some money and others.Keywords: Cipta Karya Bird Club, Community, Kicau Mania, Social Capital